Pengaruh Economic Value Added (EVA) dan Market Value Added (MVA) Terhadap Harga Saham dengan Return On Asset (ROA) Sebagai Pemoderasi - Rimbano, Dheo; Andrinaldo, Arisky; Idayati, Irma; Erha, Emma Widianti (Politeknik Ganesha Medan, 2024)
The purpose of this study was to analyze the effect of Economic Value Added (EVA and Market Value Added (MVA), on Stock Prices with Return On Asset (ROA) as a Moderating Variable in Household Appliances Sub-Sector Companies Listed on the Indonesia Stock Exchange (IDX). The independent variables used are Economic Value Added (EVA and Market Value Added (MVA). The dependent variable used is stock prices. The moderating variable used is Return On Asset (ROA). The population in this study is the Household Appliance Sub-Sector companies listed on the Indonesia Stock Exchange (IDX) in the 2000-2021 period. The sampling method used was purposive sampling method with a sample of 6 companies during the 8 year observation period. The analytical method of this study uses quantitative and moderating regression analysis. The results of this study indicate that EVA has a significant effect on stock prices. Meanwhile, ROA with EVA and MVA as moderating variables have a significant effect on stock prices.